Turkish Great Offensive in French and English resources - Uludağ, Mekki (Afyon Kocatepe Üniversitesi)
In this paper, French and English sources about the Great Offensive were evaluated. The sources of the study are the British, American and French press of the period, as well as French and English articles, journals and books on the subject. The preparation stage for the Great Offensive and the Great Offensive constitutes the scope of the study. The study’s objective is to expose the Allied sources’ accounts of the Great Offensive which led to a rout for the Greek army. The comparative analysis method was preferred in the study. Accordingly, primarily news and articles from different sources on the subject were identified, and approaches in different sources related to the same development were revealed. Finally, the news determined was included in the scope of the study after being compared with the real situation by making use of the records of the Grand National Assembly of Turkey, the news in the local press and archive documents. The most important possible findings of the study are that the information obtained by using relevant sources contributes to the literature. It can be said that the British press mostly supported the Greeks from the beginning to the end of the Greek occupation. However, it should be noted that there are many unbiased news and comments in the British press. The French press mostly tried to remain impartial, and most news critical of the British was included. The American press has tried to present objective news to a large extent, excluding a small number of news for propaganda purposes.

Bu çalışmada Büyük Taarruz ile ilgili Fransızca ve İngilizce kaynaklar değerlendirilmiştir. Çalışmanın kaynakları dönemin İngiliz, Amerikan ve Fransız basını olup ayrıca konu ile ilgili Fransızca ve İngilizce makale, dergi ve kitaplardır. Büyük Taarruz’a hazırlık aşaması ile Büyük Taarruz bu çalışmanın sınırlarını oluşturmaktadır. Çalışmanın amacı, Yunanistan’ın büyük hezimeti ile sonuçlanmış olan Büyük Taarruz’un İtilaf Devletleri kaynaklarındaki anlatımının ortaya çıkarılmasıdır. Çalışmada mukayeseli analiz yöntemi tercih edilmiştir. Buna göre öncelikli olarak konuyla ilgili farklı kaynaklardaki haber ve yazılar tespit edilmiş, aynı gelişme ile ilgili farklı kaynaklardaki yaklaşımlar ortaya çıkarılmıştır. Son olarak tespit edilen haberler, TBMM Zabıt Cerideleri, yerel basın organlarındaki haberler ve arşiv belgelerinden faydalanılmak suretiyle gerçek durum ile mukayese edildikten sonra çalışma kapsamına alınmıştır. Çalışmanın en önemli muhtemel bulguları, ilgili kaynaklardan yararlanılarak elde edilen bilgilerin literatüre katkı sağlamasıdır. İngiliz basınının çoğunlukla Yunan işgalinin başından sonuna kadar Yunanlıları destekleyen bir tutum içinde olduğu söylenebilir. Bununla birlikte İngiliz basınında çok sayıda tarafsız haber ve yorumların yer aldığını belirtmek gerekir. Fransız basını çoğunlukla tarafsız kalmaya çaba göstermiş, çoğu kez İngilizleri eleştiren haberlere yer verilmiştir. Amerikan basını, az sayıdaki propaganda amaçlı haberler hariç tutulursa, büyük oranda objektif haber sunma çabası içerisinde olmuştur.
Fransızca ve İngilizce kaynaklarda Türk Büyük Taarruzu
Keywords: Turkish Great Offensive; Afyonkarahisar; English Press; French Press; Türk Büyük Taarruzu; İngilizce Basın; Fransızca Basın